The notation of medieval music - Parrish, Carl 1904-1965 (New York Pendragon Press, 1978)
This work studies the development of musical notation from the ninth to the fifteenth century and contains sixty-two fascimiles. Originally published in 1957 this has long been the only concise study of the subject in English. For the Pendragon edition corrigenda and addenda have been incorporated into the text.